Avalanche Photodiodes in Submicron CMOS Technologies for High-Sensitivity Imaging - Betta, Gian-Franco Dalla; Pancheri, Lucio; Stoppa, David; Henderson, Robert; Richardson, Justin (IntechOpen, 2011)
None